Attitude and acceptability of assisted reproductive technology among women in a tertiary hospital in Sokoto, northern Nigeria - Umar, Amina G.; Adamu, Aisha N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Infertility couple affects the couple’s life, work, health, personality, identity and quality of life. The aim of the study is to determine the attitude and acceptability of assisted reproductive technology among women at the Usmanu Danfodiyo University Teaching Hospital, Sokoto. Methods: This is a cross-sectional study that involved three 350 women attending infertility clinic. They were recruited via convenient sampling method using semi-structured questionnaire. The data obtained was managed using the statistical package for social sciences version 20. A p value of <0.05 was considered statistically significant and the result obtained was presented in charts and tables. Results: Among the 350 women recruited, their ages ranged between 14-58 years with a modal age of 25-35 yeas (58.0%) and a mean of 28.59±6.7. They are mostly (78.6%), of the Hausa/Fulani ethnic group. Almost all (98.9%) of them were married and unto 40.5% of them were in polygamous marriage. Majority, 36.9% had tertiary education, and about same proportion, about half, 51.7%% were gainfully employed. About 60.3% of them were nulliparae with a mean duration of infertility of 5.07±4.8 years. Approximately half, 53.1% had secondary infertility and only about half, 51.4% will accept ART if offered. Unfortunately, among those who declined, majority (40.9%) had no reason for doing so. There was statistically significant association between educational status and acceptance of assisted reproductive technology (ART) at p value 0.02. Conclusions: The acceptance of ART in our environment is influenced by the educational status and number of living children.